Spherosomatometric method for analysis of anteroposterior spine curvatures in swimmers - Iwanowski, W. (Swimming II: Proceedings of the Second International Symposium on Biomechanics in Swimming, Brussels, Belgium, 1975)
A spherosomatometric study was made of the anteroposterior curvatures of the spine among competitive swimmers who had trained a minimum of 3 years. They were grouped according to the stroke in which they specialized. The study was carried out in the years 1969, 1970, and 1974. The number of individuals under study totaled 102 male and 85 female swimmers. The age of the boys ranged from 13 to 16 years, with a mean of 15.1 years. The girls' ages ranged from 11.5 to 14.5 years, with a mean of 13.8 years. Table 1 presents a summary of the number of male and female swimmers who swam each stroke.